(3eNJUQ bQI GdYjhf GdfhGXQ aj GdhLhg hGdfXGFQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI bGd GdGeGe CHhaQL GdLhRi deG LeYJ cJGH GdehShe HbQI GdYjhf GdfhGXQ s
(3BNQgG (B:s
(3Je GdcJGH hGdMeO ddg Ydi fYeg GdaGNQg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs